WASTE PICKLE LIQUOR UTILIZATION AS FECL3 COAGULANT BY ELECTROLYSIS - Adhi Nugroho, Agung
Pickling is a method typically used in a cold milling plant for eliminating impurities in hot rolled coil by immersing coil in strong acid solution. The production of spent pickle liquor could cause waste handling problem if it is not handled appropriately. Some common methods for treating spent pickle liquor are pyrometalurgy, crystallization, membrane filtration and liquid-liquid extraction. The main idea of these methods is to regenerate acid and separate it from diluted metallic ion. The abundant metallic ion could be reused as a main ingredient of coagulant Ferric Chloride. The purpose of this research is to study the kinetic profile of Fe2+ oxidation to produce FeCl3 and the best condition in conducting the WPL electrolysis. The configuration and process parameter applied in this research are based on best configuration featured in Adhi,dkk research in 2017. Electrolysis will be conducted in ambient condition with the variation of voltage (3-6 volt), electrolysis time (60-120 minutes) and addition of excess NaCl or HCl (0-50%). The run concludes that metal impurities in the WPL and the excess chlorine aren’t significantly affect the FeCl2 conversion. This research also conclude that the best condition in conducting the electrolysis process is at 6V voltage, 90 minutes reaction time, and with the excess chlorine at 0% stoichiometri.